Advanced Digital / Ammar Asbi, Edwin Antas, Harizun Mohd Halid… [et.al]. - Asbi, Ammar; Abdul Manaf, Shahrani; Mohd Talhah, Rafiqah; Antas, Edwin; Mohd Halid, Harizun (Faculty of Information Management, 2003)
This company has known as Advanced Digital Company. The form of our business is partnership by five people. The core business of this company is a supplier ICT device to university, school, tuition center, companies and others that may be use our products to make presentation and project. However we can focus to learning and teaching aspect especially in school and university. The location of our business is at 2-12 2nd Floor, Plaza Alam Central, Jalan Majlis, Seksyen 14, 4000 Shah Alam, Selangor Darul Ehsan. The factors of selecting the proposed business are to supply device and help teachers, lecturers and students and other institution to make presentation of their information in systematic way with using instructional technology tools. The products that we can supply is projector, computer and also others related products. We build this business because to take opportunity on the lack of technology tools especially in school. We take this opportunity because it has expandable and bright future and can give us more profits. We also can give a service. We hope that we can get an experience and can fulfill the need of our target customer and arrange the business properly to get more effectiveness to develop our company.